The Advantages of Numbers of English Text Books in Student’s Reading Comprehension at The Third Semester of TBI IAIN Madura - Wijayanti, Tutik; Basri, Hasan (PANYONARA: Journal of English Education, 2019)
The number of English textbooks facilitates the students in their reading comprehension process because it will help them easier in comprehending the text and increasing the student?s knowledge. This research investigates about what are the advantages of numbers of English textbooks in student?s reading comprehension at the third semester of TBI IAIN Madura (Formerly STAIN Pamekasan) and how do the numbers of English textbooks help in student?s reading comprehension. 10 students are observed. The study was conducted using narrative qualitative research. The data are gotten from observation, interview, and documentation. The result of this research shows that there were four advantages of numbers of English textbooks in student?s reading comprehension, they are as a source of knowledge, as the references, as a training to have better thinking, and as pleasure. And how the numbers of English textbooks help in student?s reading comprehension, most of the students realize that by reading several books, it helps them easier in comprehending the text, reaching higher levels of thought, add up new vocabularies, understanding reading text easily.